Acute neuromuscular and hormonal responses to 20 versus 40% velocity loss in males and females before and after 8weeks of velocity-loss resistance training - Walker, S.; Häkkinen, K.; Virtanen, R.; Mane, S.; Bachero-Mena, B.; Pareja-Blanco, F. (Experimental Physiology, 2022)
Scientific examination of velocity-based resistance training (VBRT) has increased recently, but how males and females respond to different VBRT protocols or how these acute responses are modified after a period of training is unknown. Habitually resistance-trained males and females followed either a 20 or 40% velocity-loss programme for 8weeks. Acute squat loading tests (five sets, 70% one-repetition maximum load, 3min rest) were performed before and after the training period. Tests of maximum neuromuscular performance and blood sampling were conducted before, within 10min of completion (POST) and 24h after each acute loading test. Testing included countermovement jump, resting femoral nerve electrical stimulation and bilateral isometric leg press. Blood samples were analysed for whole-blood lactate, serum testosterone, cortisol, growth hormone and creatine kinase concentrations. Countermovement jump height, maximum isometric bilateral leg-press force and the force from a 10Hz doublet decreased in all groups at POST after 20 and 40% velocity loss. Only males showed reduced force from the 100Hz doublet and voluntary force over 100ms at POST before training. The 40% velocity loss led to increased blood lactate and growth hormone responses before training in both males and females. After training, more systematic and equivalent responses in force over 100ms, force from a 100Hz doublet and blood lactate were observed regardless of sex/VBRT protocol. Overall, acute responses were greater from 40% VBRT, and males were more susceptible to acute loss in force production capacity before the training period. These VBRT protocol- and sex-related differences were diminished after training.